The Effect of Transformational Leadership, and Servant Leadership on Organizational Citizen Behavior of Nurses with Job Satisfaction as a Mediator Variable - Damayanti, Amalia Sabina; Suhartini, Suhartini (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores how transformational and servant leadership influence nurses’ Organizational Citizenship Behavior (OCB), with job satisfaction as a mediating variable. Using the quantitative method, data from 70 respondents were collected through an online questionnaire and analyzed using SEM-PLS. The findings indicate that transformational and servant leadership have a significant positive impact on job satisfaction. Transformational leadership also has a significant positive effect on OCB. However, servant leadership and job satisfaction do not significantly affect OCB. In addition, job satisfaction does not mediate the relationship between the two leadership styles and OCB. These results highlight the importance of transformational leadership in influencing OCB. Future research is suggested to add other mediating or moderating variables for deeper understanding.